Tokoh Ganjil dalam Karya Sastra Budi Darma - Wahyudi Siswanto (Humaniora, 2010)
The literary works of Budi Darma represent a successful masterpiece in the renewal efforts, especially in the field of fiction techniques and in the case of content. He represents a writer who lays open the world of anomaly. Many figures in its literary works are presented as anomalous figures. Anomalous figures in the literary works of Budi Darma can be (I) physically or seemingly physically anomalous and (2) psychologically anomalous. This article explores anomalous figures particularly those of physically or seemingly physically anomalous. The solution of the literary works is also related to the background of Budi Darma.